A Domain-Independent Interaction Integral for Dynamic Fracture in Nonhomogeneous Magneto-Electro-Elastic Materials. (14th April 2023) - Zhu, Shuai; Yu, Hongjun; Wang, Biao; Hao, Liulei; Liu, Shizhuang; Wang, Jianshan; Guo, Licheng
Abstract: In practice, magneto-electro-elastic (MEE) equipment are inevitably subjected to impact loading during service, resulting in fracture failure of the devices. This paper proposes a dynamic domain-independence interaction integral (DII-integral) to solve the dynamic intensity factors (IFs) at the crack tip of MEE materials. Here, this is a new expression of the interaction integral (I-integral) for dynamic crack study of nonhomogeneous MEE media, and we further extend it to MEE materials containing complex interfaces. Domain-independent property of the I-integral is theoretically demonstrated and excellent numerical results (relative deviation<1%) obtained from the various integration domains again verify the domain-independence for nonhomogeneous and multi-interface material properties without considering the material continuity requirements. Through the combination of the DII-integral and extended finite element method (XFEM), a good agreement is observed by comparing with the published data subjected to different MEE impact loadings. Typical examples reveal that the magnitude of dynamic mode-I stress intensity factor (SIF), dynamic electric displacement intensity factor (EDIF) and dynamic magnetic induction intensity factor (MIIF) decrease with the increase of the poling angle of the MEE material, while the dynamic mode-II SIF shows the opposite change. The peaks of dynamic EDIF and MIIF are more sensitive to the distance between the parallel cracks than the SIF, and all IFs are smaller than single crack due to the shielding effect. Finally, the significant difference on the dynamic IFs is observed with various material discontinuities. Graphical Abstract: Unlabelled Image Highlights: A new domain-independence I-integral is proposed for dynamic fracture analysis of magneto-electro-elastic materials. The DII-integral is domain-independent for nonhomegeneous and multi-interface magneto-electro-elastic material. The amplitudes of the dynamic SIFs, EDIF and MIIF are significantly affected by the polarization direction. The effects of the distance from the crack tip to interface and material discontinuity on dynamic IFs are studied.